Saturday

October 25, 2014

October 25, 2014

Posted by **frances** on Friday, May 27, 2011 at 9:22am.

- math -
**PsyDAG**, Friday, May 27, 2011 at 10:31am18x - 16 + 6( 2 - 2x) = 50

Get rid of parenthesis.

18x - 16 + 12 - 12x) = 50

Combine like terms.

6x - 4 = 50

6x = 46

x = 7.67

- math(0ops) -
**PsyDAG**, Saturday, May 28, 2011 at 3:12pm6x - 4 = 50

6x = 54

x = 9

**Answer this Question**

**Related Questions**

math - when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left ...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

Math - Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+...

Math - How can we factor trinomial: 36x^2+18x+0 Is thislike this: 18x(2x+1)

Math - 9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and...

college algebra - y intercept: 3x^2+18x 0=3x^2+18x from here im lost

Math - i'm a bit stuck with this.. 145/18 = x + x^2 what does x equal to? ...

Pre-Cal - Classify the conic and write the equation in standard form: (1) 9x^2...

math - help my daughter has a math problem and came to me for help, I am lost...

math! - determine two geometreic sequences whose first terms are 18x-9, 2x+8 and...